Outcomes of the Suture "Pull-Through" Technique for Repair of Lateral Skull Base CSF Fistula and Encephaloceles. Issue 3 (March 2017) - O'Connell, Brendan P.; Hunter, Jacob B.; Sweeney, Alex D.; Thompson, Reid C.; Chambless, Lola B.; Wanna, George B.; Rivas, Alejandro
Abstract : Objective: Describe the safety profile and surgical outcomes of a combined transmastoid-middle cranial fossa suture "pull-through" technique for repair of lateral skull base defects. Study Design: Retrospective. Setting: Tertiary care hospital. Patients: Patients undergoing surgery for cerebrospinal fluid (CSF) fistula and/or encephalocele. Intervention: Combined transmastoid and middle fossa approach using suture pull-through technique. Main Outcome Measures: The primary outcome measures of interest were recurrence of CSF fistula or encephalocele, and postoperative air-bone gap. Results: Twenty-six patients were included; mean age at surgery was 60 ± 14 years and 65% of patients were female. The majority of defects involved both the tegmen mastoideum and tympani (69%); multiple defects were present in 11 patients. Small craniotomy (2 × 3 cm) was performed and defects were repaired using composite grafts constructed with fascia, bone, and/or cartilage, and dural substitute affixed with suture. The suture tail was left long and passed from the middle fossa through the defect into the mastoid. At average follow-up of 8.3 months, no patients of recurrent CSF leak were noted. Significant improvements in both mean pure-tone average and air-bone gap were noted for the entire cohort ( p = 0.04 and p = 0.02, respectively). Conclusion: A combined transmastoid-middle cranial fossa for the repair of lateral skull base CSF fistula and encephaloceles using the suture "pull-through" technique is efficacious and the complication profile is favorable. This method facilitates reliable placement of a composite graft in the center of lateral skull base defects through a small craniotomy that minimizes temporal lobe retraction.